Effect of biochar, graphene, carbon nanotubes, and nanoparticles on microbial denitrification: A review - Li, Anhang; Yao, Jiachao; Li, Nan; Shi, Changjie; Bai, Mengwei; Wang, Zeyu; Hrynsphan, Dzmitry; Savitskaya, Tatsiana; Chen, Jun (Critical reviews in environmental science and technology, 2025)
Nitrogen pollution poses a substantial threat to water bodies, making the exploration of effective treatment technologies imperative. Among these, biological denitrification stands out as one of the most efficient methods. Various materials, including biochar, graphene, carbon nanotubes, and nanoparticles, have gained widespread use across different industries due to their unique properties. Numerous studies have investigated the impact of these materials on microbial denitrification individually, focusing on their influence on key enzymatic processes, functional genes, electron transport, functional proteins, and microbial metabolic activities. This manuscript aims to contribute a comprehensive and holistic perspective by presenting consolidated data on the collective impact of biochar, graphene, carbon nanotubes, and nanoparticles on microbial denitrification. The combination of biochar and microorganisms improves denitrification performance by 415%. Graphene increases enzyme activity (100-175.4%). The coupling of carbon nanotubes and microorganisms reduced denitrification performance by 57.42%. Nanoparticles reduce denitrification performance (73.4%), enzyme activity (63%), and electron transfer rate (52.4%) by entering the cell membrane. Moreover, these materials have been observed to induce alterations in the community structure of microorganisms involved in denitrification. The manuscript delves into the intricate details of how these materials influence the conformational changes of denitrifying enzymes, emphasizing the relationship between enzyme activity and structural modifications. Overall, this manuscript not only provides a thorough analysis of the effects of biochar, graphene, carbon nanotubes, and nanoparticles on microbial denitrification but also explores their implications for the conformational dynamics of denitrifying enzymes. Furthermore, it outlines avenues for future research, offering a roadmap to guide upcoming studies in this critical field.